Multidisciplinary Approach To Treatment Of Midline Diastema - Ghoul, Rand; Ghannam, Nidal; Shilabayeh Hanali, Abu-; Azzaldeen, Abdulgani; -Hussein Muhamad, Abu (Journal of Neonatal Surgery, 2025)
Midline diastema is a space between the maxillary and/or mandibular central incisors. Midline diastema can be due to various causes such as genetic, environmental, and so on. Proper history taking and correct diagnosis of the etiology of the diastema is essential to ensure that the orthodontic correction is successful, and no future relapse takes place. The presence of diastema between the central incisors in the adult patient has esthetics and malocclusion concerns. Treatment depends upon the correct diagnosis of its etiology and early intervention relevant to the specific etiology . The present article presents the treatment of a 9cases with midline diastema